A COMPREHENSIVE REVIEW OF MHEALTH STUDIES IN MALAYSIA: ADOPTION, USAGE, AND ATTITUDE - Jamaludin, Nurfatihah Akmal; Zamani, Zarina; Amir Nordin, Norerna Eddrina; Jamaludin, Nurshazana Akmal (Journal of Islamic, Social, Economics and Development, 2024)
This review synthesizes research from 2017 to 2023 on the adoption, usage, and attitudes towards mobile health (mHealth) in Malaysia. Key factors influencing mHealth adoption, such as performance expectancy, health literacy, and professional use, are examined alongside behavioral intentions and perceptions of various stakeholders. The findings highlight significant determinants and mediators of mHealth adoption, offering insights into areas for future research and potential interventions to enhance mHealth utilization. Recommendations include training programs for healthcare providers, developing tailored mHealth applications, and further investigating cognitive and psychological factors influencing mHealth adoption. These steps aim to support the effective integration of mHealth solutions in Malaysia's healthcare system.